Synthesis and Characterization of Electrically Conducting Polyaniline Doped with Glacial Acetic Acid (CH3COOH) at Room Temperature - Melad, Omar (Journal of Research Updates in Polymer Science, 2015)
Polyaniline (PANI) has been prepared by chemical oxidation method at room temperature and the effect of concentration of dopant Glacial Acetic Acid (CH3COOH) on the structure of the polymer was investigated. Polymers prepared in absence and in the presence of varying concentrations of CH3COOH were characterized using UV-visible, FTIR spectroscopy and conductivity measurements. In UV-visible spectra of PANIs recorded in DMSO revealed that absorption bands increases with increasing concentration of CH3COOH. The FTIR spectra shows the absorption bands related to quinoid and benzenoid rings for the undoped and doped PANI in CH3COOH indicating that the polymer is composed of amine and imine units. Highest conductivity value was obtained in presence of 1.0 M CH3COOH indicating that the more preferable doping of PANI will be at this concentration of CH3COOH. The effect of the temperature upon the conductivity of PANI synthesized with different concentrations of CH3COOH has been studied.